Shrinkage performance of fly ash alkali-activated cement based binder mortars - Kheradmand, Mohammad (2018)
Some authors reported that Alkali-activated Cement Based Binder (AACB) mortars can have much higher drying shrinkage than Portland cement based composites. Its worth remember that shrinkage performance is a very important property for reinforced concrete composites just because a high shrinkage performance is associated to cracking tendency that leads to future durability problems. Usually shrinkage is assessed under unrestrained conditions. However, the use of a restrained ellipse ring test is especially interesting for materials that will be used in restrained conditions like repair mortars. This paper provides results on restrained and unrestrained shrinkage performance of fly ash AACB mortars. The restrained shrinkage was assessed with an elliptical ring that provides a faster and more reliable assessment of the cracking potential than circular rings. The results show that the mixtures with lower sodium silicate content are associated to a lower unrestrained shrinkage. Mixtures with lower sodium silicate content showed reduced average crack width under restrained conditions. The results also show that the reduction of sodium silicate content delays the appearance of cracks and is also associated to lower crack width. The use of AACB mortars in restrained conditions requires the use of a reduced sodium silicate content or else the use of fibres to prevent crack appearance.